Using a Consultant Workshop Model to Improve Performance Management in Chinese Autism Agencies: A Preliminary Study. Issue 1 (2nd April 2020) - Westemeier, Steve; Huang, Weihe; Li, Dan
ABSTRACT: This study investigated the outcomes of using a consultant workshop model to help implement performance management (PM) methods in selected Chinese autism agencies. A need for improvement of educational services in Chinese autism agencies was identified. However, the theory and methods of organizational behavior management (OBM) in general and PM in particular are still foreign in the Chinese autism community. The primary research question of the current study was whether first-line teacher performance in Chinese autism agencies could be improved by the use of a consultant workshop model to train management staff to implement a PM system. Four autism agencies in different Chinese provinces participated in this study. Results demonstrated that after the implementation of the PM system through a consultant workshop model in the participating agencies, the performance of first-line teachers in these agencies improved in several important areas. The intervention appeared modestly effective. Implications of the outcome data and future directions for practitioners and researchers are discussed.